DAMPAK KEBIJAKAN PENGEMBANGAN BAHAN BAKAR NABATI TERHADAP DINAMIKA HARGA KOMODITAS PANGAN DAN ENERGI NASIONAL DENGAN PENDEKATAN MODEL SISTEM DINAMIS - Eka Denny M; Nunung Kusnadi; Mangara Tambunan; M Firdaus (Indonesian Journal of Agricultural Economics, 2011)
The increasing consumption of fossil fuels and the limitation of its availability are twomajor causes of the fluctuating trends of fossil fuels prices. They are also believed tohave created instability of certain feedstock prices since alternative energy used as thesubstitution of fossil fuels is based on this feedstock as well.This research is aimed onreviewing the correlation between the dynamic movement of the prices of crude palmoil (CPO) which is used in the production of biodiesel and the government policy ondeveloping renewable fuels using dynamics system approach. In particular, this researchwill examine whether policy to try increase CPO export tax to 20 % and to allocate 50%of CPO production for domestic need will influence the effort of fullfilling mandatorytarget for biodiesel to contribute at least 5% of the total national energy consumption by2025 and CPO prices trends.Keyword: dynamics system, CPO, biodiesel, fossil fuel